Educação infantil e relações de gênero : o que se inscreve nos corpos infantis? - Souza, Gislene Cabral de (2015)
This research takes part in the Childhood, Youth and Contemporary Culture Group Research, that integrates the research line “Language, culture and knowledge construction: historical and contemporary perspectives”. Its principal aim is to understand gender relations in the ways children interact in the context of early childhood education, based on the following questions: what artifacts, objects, images are significant for children and circulate among them in different spaces and times from school? That time and space are used and created by children to share practices that lead to gender relations? Children establish relationships with one's own body and the body of the other, which are marked by gender issues? As the friendly relations are crossed by these issues? We have the school as a social space of tensions, which, on the one hand, reproduces models, on the other, constitutes as a privileged terrain of discussions and breaking taboos, bringing children the opportunity to question the dominant patterns of relate to emotional and social. The research was conducted in a Municipal School of Early Childhood Education (EMEI) Rondonópolis, Mato Grosso, in a class of 2nd 2nd Cycle grouping, with the subject an effective educator of municipal, graduated public in Pedagogy, and 20 children aged between 5 and 6 years. It has been as a methodological strategy participant observation of children everyday in school, with a view to analysis of gender relations in the ways they relate in the context of early childhood education with your body and the body of another during play, dialogues and the choices of school artifacts. Using methodological procedures of ethnographic qualitative research, this research has also met with femininity and masculinity that are produced in school. In this sense, it is observed that, in their gender relations, children learn socially patterned behaviors that impact on their ways to be boy and girl. It appears that the discourses present in the classroom are guided by binary relations, which mark the times, spaces and objects belonging to boys and girls. Still, despite all the strategies to suit children to normative patterns of behavior has been observed that there are situations in which children express resistance to imposed on them, either through disputes, confrontations or leaks, demonstrating that there are always possibilities to build other ways of being and to act with respect to gender.